KEPERCAYAAN MASYARAKAT TOONO – IWATE TERHADAP MISTERI MAYOIGA DALAM TOONO MONOGATARI KARYA YANAGITA KUNIO - Kentaro, Kaneko; Muzakka, Moh; Mulyadi, Budi (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2016)
Toono Monogatari is a folklore that has become a tradition in Toono – Iwate. In Toono Monogatari researcher examine the Mayoiga legend, which is a mysterious house in the middle of Toono forest. This study uses a reception analysis of literature and analysis of folklore to determine the responses of readers to believe in Mayoiga legend and what functions of the legend on Toono’s society. The method for obtaining data by distributing questionnaires to 33 respondents of the Japanese and in-depth interviews in the field on research directly in Toono – Iwate, Japan. While the result is that the legend Mayoiga is still believed by some of Toono’s people, and results of research to the folklore is that the Mayoiga legend has a function and an important role in the preservation of the legend, literature, and culture of the city of Toono, with this legend can boost the varieties of Toono’s culture in the city, especially in the field of tourism and research of literature and folklore.